2013
DOI: 10.1186/1752-1505-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatal and non-fatal injuries due to intentional explosions in Nepal, 2008-2011: analysis of surveillance data

Abstract: BackgroundNepal is one of the post-conflict countries affected by violence from explosive devices. We undertook this study to assess the magnitude of injuries due to intentional explosions in Nepal during 2008-2011 and to describe time trends and epidemiologic patterns for these events.MethodsWe analyzed surveillance data on fatal and non-fatal injuries due to intentional explosions in Nepal that occurred between 1 January 2008 and 31 December 2011. The case definition included casualties injured or killed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…25 Those injured or killed by intentional explosions in Nepal (2008–2011) were also disproportionately male, with males representing 78.0% of the 437 casualties. 26 Among males, the data suggest that explosions disproportionately affected those 20–39 years of age; this group accounted for 61.5% of deaths among those with known age in this study, despite accounting for only 15.6% of the Iraqi population. 21 While global estimates have limited age disaggregated data, available studies have consistently shown this age group to be at increased risk.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…25 Those injured or killed by intentional explosions in Nepal (2008–2011) were also disproportionately male, with males representing 78.0% of the 437 casualties. 26 Among males, the data suggest that explosions disproportionately affected those 20–39 years of age; this group accounted for 61.5% of deaths among those with known age in this study, despite accounting for only 15.6% of the Iraqi population. 21 While global estimates have limited age disaggregated data, available studies have consistently shown this age group to be at increased risk.…”
Section: Discussionmentioning
confidence: 57%
“…An increasing number of injuries also occurred at workplaces. Compared with explosions occurring on roads and other open-air spaces, those in enclosed spaces have been found to result in a higher number of those injured and increased severity and mortality 27 28 In open-air explosions, the explosion is likely to be fatal only if the victims are in close proximity to the device when it detonates 27 …”
Section: Discussionmentioning
confidence: 99%
“…A wide range of paediatric mortality is reported following mine strikes, ranging from 4% from 46% 24–29 31 32 55 56. Shuker57 suggested that approximately half of paediatric victims die within minutes of mine explosion, likely due to penetrating head injury, and catastrophic haemorrhage causing non-survivable injuries, in keeping with adult literature 53 54.…”
Section: Resultsmentioning
confidence: 88%
“…Similarly, prevalence of lower limb injuries shows variation between studies on blast affecting 25%–86% of children,19 22–24 35 45 46 59 65 68 69 82 with landmine strikes particularly associated with lower limb injury22–24 ; 20%–29% required operative amputations, normally at the transtibial plane 23 34 65. Lower limb injuries were less common in children compared with adults,25 27–29 56 with incidence lowest in 0–3 year olds,16 while increasing in adolescents to mirror adults 25. Traumatic amputations were less frequent compared with the upper limb, occurring in 14%–35% of lower limb injuries 24 35 69…”
Section: Resultsmentioning
confidence: 99%
“…2 Injuries due to the improvised explosive devices (IED) were also common during the 13 years conflict period in Nepal and still prevail. [5][6][7] The most common form of IED included Socket, Sutali, and Pressure cooker bombs. 5 Literature regarding accidental domestic pressure cooker injuries mostly include ocular injuries, penetrating facial injuries and traumatic brain injuries.…”
Section: Discussionmentioning
confidence: 99%